PRINT AND ONLINE NEWS REVIEWS DURING 2021 THAT INFLUENCE THE INDONESIAN DEMOCRACY INDEX IN BLITAR CITY - Zainal Abidin Achmad; Syifa Syarifah Alamiyah; Agus Wahyudi; Dinda Rizki Anita; Vieri Samuel Juliando Pakpahan (JWP (Jurnal Wacana Politik), 2023)
This study aims to analyze news content in print and online media during 2021, which affects the Indonesian Democracy Index in Blitar City. The research subjects are news from January 1 to December 31, 2021, from the print media Radar Blitar and Memorandum, as well as online media from Bhirawa.com and Mayangkaranews.com. These four media have the highest number of readers in Blitar City. This study uses a qualitative method with a textual analysis approach and collects data through virtual searches, clippings, focus group discussions, and in-depth interviews. All Informants were determined based on the representation of the institutions contained in the measurement of the Indonesian Democracy Index. The results of a review of print and online news media during 2021 show that civil liberties, political rights, and democratic institutions in Blitar City show excellent performance.